Correlation Meaning of Inheritance Arrangement in Kutuh Village - Putri, I Gusti Ayu Vina Widiadnya; Juniartha, I Wayan; Putra, I Gusti Ngurah Bagus Wahyu Nugraha (Soegijapranata Catholic University, 2023)
This study aims to analyse the text of national law and the text of customary law on inheritance. This research is a forensic linguistic study to find the correlation of meaning between national legal texts and customary law texts and their implementation in society. The approach in this study is a qualitative research approach with text analysis. The method used is observation, recording, and interviews with community leaders in Kutuh village. The observation method with note-taking technique was carried out to find the correlation of meaning in national legal texts with customary law texts. The conversant method with face-to-face technique was carried out to find out the implementation of the legal text that governs indigenous peoples in the Kutuh village. The problems were analysed using the theory of forensic linguistics and supported by the theory of meaning. The result of this research is a positive correlation between national legal texts and customary law texts based on the meaning of the words in the text regulations on community inheritance rights. In addition, a positive correlation was also found in the implementation of customary law texts in the community.